STUDENTS’ LIVED EXPERIENCE OF SOCIAL ADJUSTMENT IN INTERNATIONAL CREDIT TRANSFER PROGRAM: A PHENOMENOLOGICAL STUDY - Nurhayati, Nurhayati; Maulina, Maulina; Faridawati, Faridawati (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2024)
This study aims to look into the social experiences of students in the seventh semester of Universitas Muhammadiyah Kendari's English language education program who have completed the International Credit Transfer program at Nueva Ecija University of Science and Technology in the Philippines. A phenomenological research design was used to conduct the study. The participants of this study were four students. Two of the four students were male, while the other two were female. Semi-structured interviews were conducted face-to-face with each participant. The findings showed that the ICT program provided the students with valuable experiences that broadened their perspectives, improved communication skills, and enhanced their ability to accept and adapt to diverse social environments.